Functional respiratory imaging, regional strain, and expiratory time constants at three levels of positive end expiratory pressure in an ex vivo pig model. Issue 23 (6th December 2016) - Henderson, William R.; Molgat‐Seon, Yannick; Vos, Wim; Lipson, Rachel; Ferreira, Francisca; Kirby, Miranda; Holsbeke, Cedric Van; Dominelli, Paolo B.; Griesdale, Donald E. G.; Sekhon, Mypinder; Coxson, Harvey O.; Mayo, John; et al.
Abstract: Heterogeneity in regional end expiratory lung volume (EELV) may lead to variations in regional strain ( ε ). High ε levels have been associated with ventilator‐associated lung injury (VALI). While both whole lung and regional EELV may be affected by changes in positive end‐expiratory pressure (PEEP), regional variations are not revealed by conventional respiratory system measurements. Differential rates of deflation of adjacent lung units due to regional variation in expiratory time constants ( τ E ) may create localized regions of ε that are significantly greater than implied by whole lung measures. We used functional respiratory imaging (FRI) in an ex vivo porcine lung model to: (i) demonstrate that computed tomography (CT)‐based imaging studies can be used to assess global and regional values of ε and τ E and, (ii) demonstrate that the manipulation of PEEP will cause measurable changes in total and regional ε and τ E values. Our study provides three insights into lung mechanics. First, image‐based measurements reveal egional variation that cannot be detected by traditional methods such as spirometry. Second, the manipulation of PEEP causes global and regional changes in R, E, ε and τ E values. Finally, regional ε and τ E were correlated in several lobes, suggesting the possibility that regional τ E could be used as a surrogate marker for regional ε . Abstract : We used functional respiratory imaging (FRI) in an ex‐vivo porcine lung model to: (i) demonstrate that computed tomography (CT)‐based imaging studies can be used to assess global and regional values of ε and τ E and, (ii) demonstrate that the manipulation of positive end‐expiratory pressure will cause measurable changes in total and regional ε and τ E values.